An uncommon formation type of adjectives that denote an incomplete degree of quality: ʿpãjuodis’ and ʿpasaũsis’ - Tamulionienė, Aurelija (Lietuvių kalba, 2011)
The article deals with adjectives that denote an incomplete degree of quality and that are made of a base adjective plus the prefix pa- plus an ending -is and that belong to the first and second accentual paradigms. The study focuses on the following aspects: geographical distribution, accentuation, word formation and semantics. In some cases of this formation type, the dominant intensifying prefix pa- acquires stress and maintains or intensifies the strength of the base stem, whereas in other cases it intensifies the base stem but remains unstressed. Despite the differences in accentuation the derivatives of this kind can be ascribed to the same word-formation type as their accentuation has most probably been affected by the geographical distribution. The study has shown that they are used in different regions that are remote from each other, i.e. in the sub-dialects of Northern Žemaitian kretingiškiai, Southern Žemaitian varniškiai and Eastern Aukštaitian panevėžiškiai. The same derivatives of the word-formation type of adjectives under investigation are also used in ancient writings. They usually have only one meaning. In the Lithuanian Language Dictionary their meaning is typically explained by providing synomyms, in less common cases – by giving reference to another word or by means of description. The majority of the adjectives under investigation retain the core meanings of the base.
Keywords: none